Efficacy of international approaches to medicine price regulation and control: A scoping review - Mohammad Bashaar, Mohamed Azmi Hassali, Fahad Saleem, Alian A ALrasheedy, Vijay Thawani, Zaheer-Ud-Din Babar (Journal of Applied Pharmaceutical Science, 2017)
Background: The access to affordable medicines is counted as a challenge, despite international measures taken towards cost containment and price regulation. Objective: To identify and review the literature on international approaches related to medicine price regulation, control, and its effectiveness. Methods: In this scoping review, peer-reviewed research and review articles, discussion papers, public documents relating to medicine pricing policies were reviewed. The search strategy was structured according to STARLITE principles. The key search terms and phrases were “medicine prices”, “causes of high medicine prices”, “ approaches towards medicine prices control”, “national medicine policies”, “international approaches towards medicine price control”, “containment policies”, and “effects of pricing policy on medicine”. Results: Medicine pricing and price regulation policies were drafted and implemented with no optimal results and things don’t seem to have improved much and remain as the distant goal. These policies were either less comprehensive, outdated and fell short in implementation especially in low and middle-income countries (LMICs) due to lack of funding, infrastructure or trained professional task force. Overall, none of the policy options was preferred. Multi-pronged policy options crafted in local context are required to tackle the issue. Conclusion: The authors identify gaps in the literature and propose advanced research in the area to strengthen the healthcare system by improving medicine pricing system in each country.
Keywords: Medicine Price, Regulation,Price Control, Medicine Policy.